Implementasi Model Pembelajaran Cooperative Learning Tipe STAD untuk Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran IPA di SMP Negeri 1 Kayangan - Israil, Isnawati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The purpose of this study was to increase student motivation in learning science through the implementation of the STAD type cooperative learning model in SMP Negeri 1 Kayangan. The research method used was classroom action research with 28 students as subjects. The research instrument used was an observation sheet. The analysis of the data of this research used descriptive qualitative and qualitative analysis techniques. The result of this study showed that the implementation of the STAD type cooperative learning model in learning science in the material elements, compounds, and mixtures could increase student motivation. It could be indicated by an increase in the percentage of the students’ learning mastery in cycle II in class VII SMP Negeri 1 Kayangan.